2006
DOI: 10.1007/11758549_141
|View full text |Cite
|
Sign up to set email alerts
|

Data Replication Techniques for Data-Intensive Applications

Abstract: Abstract. Several data replication techniques have been developed to support high-performance data accesses to the remotely produced scientific data. Most of those techniques, however, do not provide the replica consistency because the data replica is just periodically updated through the remote clients. We have developed two kinds of data replication techniques, called owner-initiated replication and client-initiated replication. Our replication techniques do not need to use file system-level locking function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For the sake of showing the applicability of this mechanism, they also investigated that their system is able to achieve a smooth tradeoff between performance and availability [24]. No et al affirmed that data replication techniques can benefit to support better data accesses to the required scientific data and proposed ownerinitiated replication and client-initiated replication mechanisms to provide data consistency [25]. Moreover, recent works in a replicated parallel file system [19], [20] have demonstrated that there are a great room for improving I/O throughput and data durability and availability by employing data replication and idle storage.…”
Section: Related Workmentioning
confidence: 99%
“…For the sake of showing the applicability of this mechanism, they also investigated that their system is able to achieve a smooth tradeoff between performance and availability [24]. No et al affirmed that data replication techniques can benefit to support better data accesses to the required scientific data and proposed ownerinitiated replication and client-initiated replication mechanisms to provide data consistency [25]. Moreover, recent works in a replicated parallel file system [19], [20] have demonstrated that there are a great room for improving I/O throughput and data durability and availability by employing data replication and idle storage.…”
Section: Related Workmentioning
confidence: 99%